Passion - Kate, Lauren (New York : Delacorte Press, 2012)
Reveals background information about the lives of Luce and her fallen angel boyfriend, Daniel, and provides insight into centuries' worth of dangerous love.
Prequel to: Fallen and Torment.
Horn Book, April 2012
Young Adult
Young Adult.
Horn Book
HL 730
Keywords: Supernatural -- Juvenile fiction; Reincarnation -- Juvenile fiction; Angels -- Juvenile fiction; Supernatural -- Fiction; Reincarnation -- Fiction; Angels -- Fiction; Love -- Fiction; Supernatural -- Fiction; Reincarnation -- Fiction; Angels -- Fiction; Love stories; Love stories